An intelligent spectrum handoff scheme based on multiple attribute decision making for LTE-A network - Abdulraqeb Alhammadi; Mardeni Roslee; Mohamad Yusoff Alias; Khalid Sheikhidris; Yong Jun Jack; Anas Bin Abas; Kesh. S. Randhava (Institute of Advanced Engineering and Science, 2019)
Cognitive radio networks (CRNs) play an important role in wireless communications which have the ability to significantly utilize the spectrum that not in used and reduce the current spectrum scarcity. CR allows unlicensed users (secondary users) to occupy the licensed spectrums without causing interference with licensed users (primary users). This can be achieved smoothly through four main CR procedures: spectrum sensing, spectrum decision, spectrum sharing, and spectrum mobility. In this paper, we propose an intelligent spectrum handoff (SH) scheme based on multiple attributes decision making. The handoff decision depends on three considered parameters: received power, traffic load and arrival rate of the primary users. The simulation results show the proposed scheme outperformed the conventional scheme by reducing the probability of SH which leads to improve system performance.